2021
DOI: 10.1186/s12891-021-04458-4
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid and teriparatide have a complementary therapeutic effect on aseptic loosening in a rabbit model

Abstract: Background Revisions are mainly caused by wear debris-induced aseptic loosening. How to effectively suppress debris-induced periprosthetic osteolysis has become an urgent problem. Both zoledronic acid and teriparatide can increase the bone mass around prostheses and increase the stability of prostheses. A hypothesis was proposed: the combination of the two drugs may have a better treatment effect than the use of either drug alone. Methods We create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Several nationwide clinical studies clarified that bisphosphonate in patients with THA exhibited a lower risk for revision surgery, indicating that bisphosphonate use is encouraged in patients suffering from osteoporosis and candidates for THA ( 25 , 36 ). Animal studies also proved that both local and system administrations of bisphosphonate displayed a capacity to prevent particle-induced osteolysis by diminishing bone loss and fiber formation ( 18 , 19 , 32 ). In this study, the systemic administration of ZOL has not improved implant anchorage compared with the O+T group.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Several nationwide clinical studies clarified that bisphosphonate in patients with THA exhibited a lower risk for revision surgery, indicating that bisphosphonate use is encouraged in patients suffering from osteoporosis and candidates for THA ( 25 , 36 ). Animal studies also proved that both local and system administrations of bisphosphonate displayed a capacity to prevent particle-induced osteolysis by diminishing bone loss and fiber formation ( 18 , 19 , 32 ). In this study, the systemic administration of ZOL has not improved implant anchorage compared with the O+T group.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, intermittent parathyroid hormone (PTH) 1-34 is another classical mediation for the treatment of osteoporosis, with the capacity of anabolic effects. Our and other research groups have revealed that intermittent PTH treatment could prevent particle-induced osteolysis in vivo ( 17 19 ). Recently, several cases reported that PTH has a protective effect on prosthetic loosening clinically ( 20 22 ).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Particulate wear debris from implants can spread in the joint cavity and surface, and induce intricate biological responses including PPO and aseptic loosening [ 27 ]. As we know, wear particle can stimulate macrophages, T lymphocytes, fibroblasts, and foreign body giant cells to secrete TNFα, IL-1β, IL-6, prostaglandin E2, and other proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Surface engineering of the implant is a key strategy in overcoming aseptic loosening and research is being directed towards novel materials or enhancement of existing materials by doping with active materials that control osteoclasts and enhance osteoblast formation. [11][12][13] Current non-cemented knee or hip implants are generally cobalt-chromium or titanium alloys, often with a pre-deposited hydroxyapatite (HA) coating for improved osteointegration. [14,15] Inorganic doping of HA with elements such as strontium, silver, europium and zinc can induce a preferential biological response.…”
Section: Introductionmentioning
confidence: 99%